1991
DOI: 10.1002/tea.3660280906
|View full text |Cite
|
Sign up to set email alerts
|

Development of explanation: Incremental and fundamental change in children's physics knowledge

Abstract: In contrast to predictions or actions, explanations require articulating a model that accounts for the physical phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 9 publications
4
62
0
1
Order By: Relevance
“…A more general developmental achievement relates to understanding causality in physical systems. Several studies have demonstrated that during these years, one can observe a shift in understanding causality from a global-functional framework to one that searches for specific local trains of cause-and-effect in the components of the system (Piaget 1956;Metz 1991;Lehrer and Schauble 1998). It would seem that during this sensitive time, it would be most opportune to support children in creating alternative schemas of causality, rather than locking into a single schema of a ''direct'' chain of sequential cause-and-effect links.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more general developmental achievement relates to understanding causality in physical systems. Several studies have demonstrated that during these years, one can observe a shift in understanding causality from a global-functional framework to one that searches for specific local trains of cause-and-effect in the components of the system (Piaget 1956;Metz 1991;Lehrer and Schauble 1998). It would seem that during this sensitive time, it would be most opportune to support children in creating alternative schemas of causality, rather than locking into a single schema of a ''direct'' chain of sequential cause-and-effect links.…”
Section: Resultsmentioning
confidence: 99%
“…The research literature refers to a number of dyads describing people's stance toward artifacts: animate or human-like intention versus inanimate technological purpose (Ackermann 1991;Turkle 1984;Scaife and van Duuren 1995;Okita and Schwartz 2006;Bernestein and Crowley 2008;Jipson and Gelman 2007); function versus mechanism (Piaget and Inhelder 1972;Granott 1991;Metz 1991;Levy and Mioduser 2008); function versus physical appearance (Kemler Nelson and 11 Swarthmore College Students 1995; Diesendruck et al 2003) and original (designer's) intended function versus current function (Bloom 1996;Matan and Carey 2001;Defeyter 2003).…”
Section: Conception Of Artificial Adaptive Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have used the gear domain as a starting point and context for learning. For example, Metz (1991) explored how elementary children think about gears through the use of physical models. Children constructed a variety of gear arrangements on a gearboard and used a "think out loud" strategy to explain what they were doing and thinking.…”
Section: Background To the Studymentioning
confidence: 99%
“…The role and effect of explanations in science education and school science (Metz, 1991) have gained recognition and attention has now been directed to explanations within the context of teaching and learning (Knowles, 1990;Ruben, 1993). Studies of scientific explanations from various perspectives have resulted in investigations into how these scientific explanations may be transformed into effective teaching explanations.…”
Section: Explanatory Behaviourmentioning
confidence: 99%